USING WALNUT SHELLS AS AN ALTERNATIVE ENERGY SOURCE - PRYSIAZHNIUK, DMYTRO; GUDZENCO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The feasibility of using walnut shell as an alternative energy source is substantiated in the context of the growing deficit of conventional energy resources, rising energy prices, and the need to reduce negative environmental impacts. The paper analyzes the current state and prospects of utilizing agricultural residues in the bioenergy sector, with particular emphasis on by-products of walnut processing. The physical, energy, and environmental characteristics of walnut shell are presented, confirming its high calorific value, low ash content, and environmental safety during combustion compared to traditional solid fuels. Special attention is paid to the technological aspects of preparing walnut shell for energy use, including the influence of particle size distribution, moisture content, and the application of binding agents on the physical-mechanical and energy performance of fuel briquettes. The effect of grinding degree on bulk density, briquette strength, combustion stability, and specific energy output is analyzed. Rational moisture ranges that ensure effective densification while minimizing energy losses during drying are identified. The role of natural and auxiliary binders in improving briquette integrity and operational reliability during transportation, storage, and combustion is also considered. Based on experimental and analytical assessments, an optimal fractional composition of raw material and rational briquetting conditions are determined, providing improved energy efficiency, mechanical strength, and stable combustion characteristics of the produced biofuel. The results demonstrate that walnut shell is a promising renewable energy resource capable of partially replacing fossil fuels. The proposed technological solutions can be effectively applied in the agro-industrial and municipal sectors, contributing to sustainable energy development, waste minimization, and reduction of greenhouse gas emissions.